PROPOSED ARCHITECTURE AND THE DEVELOPMENT OF NFCAFE: AN NFC-BASED ANDROID MOBILE APPLICATIONS FOR TRADING TRANSACTION SYSTEM IN CAFETARIA - Fikrul Arif Nadra; Heri Kurniawan; Muhammad Hafizhuddin Hilman (Jurnal Ilmu Komputer dan Informasi, 2013)
The development of mobile technology and RFID leads to an innovative mobile payment technology by using NFC. One of the popular mobile device platforms today is Android. This research proposes an architecture of NFC-based payment system in cafeteria which is called NFCafe and the implementation of it in Android applications. It is a closed payment systems without involving third parties such as banks. The security issue is handled by using symmetric and asymmetric encryptions, they are RSA and AES. The application has been developed and successfully passed the testing conducted by several respondents.